Legal Accountability of Legal Subjects in the Criminal Act of Human Trafficking - Rio Saputra Manullang; Janpatar Simamora; Lesson Sihotang (Dinasti Research, 2025)
Corporate human trafficking crimes represent a serious issue involving human rights violations in Indonesia and other countries. Although Indonesia has regulated this crime through Law No. 21 of 2007 on the Eradication of Human Trafficking (PTPPO), the enforcement of laws against human trafficking still faces significant challenges. This study aims to analyze the legal responsibility of corporations as subjects of law in human trafficking crimes and to understand the mechanisms of penalization against corporations involved in such crimes. The research method used is normative juridical with a literature study approach, gathering data from primary sources such as regulations and secondary sources including books, journals, and relevant literature. Data analysis is conducted deductively, beginning with fundamental legal principles applied to the phenomenon of human trafficking crimes. The study's findings show that corporations can be held collectively criminally liable if the crime is committed by their members acting on behalf of and in the interest of the corporation. The PTPPO law expands legal accountability for corporations to ensure more effective prevention and deliver justice for victims. Penalties that can be imposed on corporations include fines, imprisonment, and other social sanctions, focusing on direct, indirect, and leadership responsibilities. This study concludes that the implementation of criminal liability against corporations aims to encourage ethical corporate behavior, protect human rights, and strengthen global efforts to combat human trafficking.